A zonal approach for estimating pressure ratio at compressor extreme off-design conditions. (April 2019) - Galindo, José; Navarro, Roberto; García-Cuevas, Luis Miguel; Tarí, Daniel; Tartoussi, Hadi; Guilain, Stephane
Zero-dimensional/one-dimensional computational fluid dynamics codes are used to simulate the performance of complete internal combustion engines. In such codes, the operation of a turbocharger compressor is usually addressed employing its performance map. However, simulation of engine transients may drive the compressor to work at operating conditions outside the region provided by the manufacturer map. Therefore, a method is required to extrapolate the performance map to extended off-design conditions. This work examines several extrapolating methods at the different off-design regions, namely, low-pressure ratio zone, low-speed zone and high-speed zone. The accuracy of the methods is assessed with the aid of compressor extreme off-design measurements. In this way, the best method is selected for each region and the manufacturer map is used in design conditions, resulting in a zonal extrapolating approach aiming to preserve accuracy. The transitions between extrapolated zones are corrected, avoiding discontinuities and instabilities.